The Association Between Level Of Depression And Fall Risk In Elderly - Da Christ, Alexandre GFH; Wattimena, Inge; Daeng, Bonaventura H (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Introduction: The prevalence of accidental falls rises as age increases. Mental issues also contribute to the increase risk of falling. Depression is one of the mental health illness that usually occur in elderly. This can worsen the physical condition and increase morbidity and mortality rate in elderly. Aim: To investigate the association between level of depression measured using GDS (Geriatric Depression Scale) and fall risk measured using MFS (Morse Fall Scale) in elderly. Methods: This research was held in Griya Lanjut Usia St. Yosef, and Rumah Usiawan Panti Surya Surabaya. The geriatric depression scale was used during this research to measure the level of depression and Morse Fall Scale to measure falling risk. This research is an analytic survey with cross sectional study design. Statistical analysis was performed using Pearson chi-square test and lambda correlation test. Results: There is a significant association between level of depression measured using GDS and fall risk in elderly measured using MFS with p=0,000 (p